Aquazol as a binder for retouching paints. An evaluation through analytical pyrolysis and thermal analysis. (October 2017) - La Nasa, J.; Di Marco, F.; Bernazzani, L.; Duce, C.; Spepi, A.; Ubaldi, V.; Degano, I.; Orsini, S.; Legnaioli, S.; Tiné, M.R.; De Luca, D.; Modugno, F.
Abstract: Aquazol poly (2-ethyl-oxazoline) is a tertiary aliphatic amide, with physical and chemical properties that are exploited in a variety of ways, from pharmaceutical applications to the conservation of cultural heritage. In this study, we evaluated the use of Aquazol as a new binder for retouching paint in the restoration of artworks. Aquazol 500 admixed with various formulations of organic red pigments was used to prepare paint replicas which were artificially aged and investigated by a multi-analytical approach based on analytical pyrolysis coupled with gas chromatography and mass spectrometry (Py-GC/MS), and thermogravimetry (TG), complemented by FTIR and LIBS spectroscopy. This is the first study on the ageing phenomena of Aquazol 500 using analytical pyrolysis and thermogravimetric analysis. The influence of the pigments' components on the pyrolysis behavior of Aquazol was also investigated. The paint replicas did not show significant modifications during artificial ageing. This thus highlights the optimal properties of Aquazol 500 as a binder for retouching, in addition to its already established suitability as a filler or consolidant in the restoration of artifacts. Interestingly, when Aquazol 500 is used in formulations containing organic pigments, Aquazol-pigment interactions are observed, strongly depending on the pigment used.